1994
DOI: 10.1259/0007-1285-67-796-342
|View full text |Cite
|
Sign up to set email alerts
|

Parotid and parapharyngeal tumours: tissue characterization with dynamic magnetic resonance imaging

Abstract: Prospective studies were performed to characterize parotid and parapharyngeal tumours using dynamic magnetic resonance (MR) imaging. Bolus injection of gadopentetate dimeglumine and a short SE sequence were used to evaluate 23 masses including seven pleomorphic adenomas, seven Warthin's tumours and nine malignant tumours. Contrast enhancement profiles helped to distinguish the different types of parotid and parapharyngeal tumours. Gradual increase in intensity during the first 260 s after the injection was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 3 publications
1
35
0
Order By: Relevance
“…One of the reasons for the inconsistencies among past studies might be their small sample sizes; with one exception, 6 each analysed only 20-50 cases. [8][9][10][11][12][13][14][15][17][18][19][20] Another reason may be the differences in imaging protocols used to obtain DCE-MRI data sets. For obtaining accurate TICs, dynamic sequences with high temporal resolutions should be applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons for the inconsistencies among past studies might be their small sample sizes; with one exception, 6 each analysed only 20-50 cases. [8][9][10][11][12][13][14][15][17][18][19][20] Another reason may be the differences in imaging protocols used to obtain DCE-MRI data sets. For obtaining accurate TICs, dynamic sequences with high temporal resolutions should be applied.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain accurate TICs, a dynamic MRI sequence with high temporal resolution should be used. 6,16 However, the temporal resolution in most of the previous studies was relatively low (15-60 s), [8][9][10][11][12]14,[17][18][19][20] which may partly explain the inconsistencies between reports.…”
Section: The Authors Phong Dai Lam and Ami Kuribayashi Equally Contrimentioning
confidence: 99%
“…It has been reported that dynamic contrast-enhanced MRI (DCE-MRI) is useful for the differential diagnosis of some tumors, and many investigators have attempted to use it to identify differences between benign and malignant tumors, as well as to assess the malignancy of tumors [3][4][5][6]. We have also reported the usefulness of DCE-MRI for tumor diagnosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Extension of tumors from the deep lobe of a parotid gland is distinguishable from tumor arising anew in parapharyngeal space by a fine translucent line representing the compressed layer of fibroadipose tissue between the tumor and deep lobe of parotid [15]. MRI has been shown to be superior to computed tomography in the investigation of parapharyngeal space tumors [16,17]. Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are the cornerstone in the initial evaluation.…”
Section: Discussionmentioning
confidence: 99%